School-based interventions for resilience in children and adolescents: a systematic review and meta-analysis of randomized controlled trials - Cai, Chenyi; Mei, Zhengyang; Wang, Zirui; Luo, Shi (Frontiers in Psychiatry, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the overall efficacy of school-based interventions (SBIs) in promoting resilience in children and adolescents and to provide evidence for advancing mental health care for children and adolescents.MethodsA search was conducted in seven electronic databases, including PubMed, Embase, EBSCOhost, Scopus, Web of Science, APA PsycINFO, and Google Scholar. The Revised Cochrane risk-of-bias tool for randomized trials (RoB 2) was used for the quality appraisal. The standardized mean difference (SMD; Cohen’s d) combined with 95% confidence intervals (CIs) was used to pool the effect sizes.ResultsA total of 38 RCTs involving 15,730 participants were included in the systematic review, 21 of which were selected for inclusion in the meta-analysis. In terms of quality appraisal, the included trials were classified as having low risk, some concerns, or high risk, with proportions of 5.2%, 71.1%, and 23.7%, respectively. The pairwise meta-analyses indicated that SBIs significantly enhanced resilience in children and adolescents compared to the control group (SMD = 0.17, 95% Cl 0.06–0.29, p < 0.01).ConclusionsSBIs have a positive effect on the resilience of children and adolescents. In the context of limited medical resources, SBIs could serve as a promising approach to promote the ability of children and adolescents to adapt to stressors. Given the considerable heterogeneity identified, SBIs should be personalized on the basis of variations in demographic characteristics, intervention implementation, and actual dose-response to improve the overall well-being of children and adolescents and reduce the risk of maladaptive psychological and behavioral responses.